Desain E-Smart Inclusive Sebagai Sistem Informasi Manajemen Pendidikan Inklusif - Erfan Kurniawan; Siti Zulaikha; Desi Rahmawati (Risenologi, 2022)
This study aims to design E-Smart Inclusive as a basis for developing a website-based inclusive education management information system so that inclusive schools can be created that are friendly to all students. The E-Smart Inclusive design was developed from the Kemendikbud RI Dapodik, foundation websites, inclusive education guidebooks, and previous research. This research refers to the Borg & Gall development model in stages one to three. Starting from the data collection stage through interviews and library studies, the planning stages of E-Smart Inclusive, and the initial product development stages of E-Smart Inclusive. The results of the research that has been carried out can be drawn a conclusion that researchers have designed E-Smart Inclusive as a basis for developing a website-based inclusive education management information system through the stages of development from Borg & Gall. At the data collection stage, the researcher conducted a literature study and interviews. The literature study was carried out through previous research, guidebooks for the implementation of inclusive education, the Kemendikbud RI dapodik website, foundation websites. Interviews were conducted with Special Education Teachers at SMPN 259 Jakarta and the Segar Amanah inclusive school. At the planning stage of E-Smart Inclusive, researchers made a list of E-Smart Inclusive features, namely the homepage feature, about us, inclusive education data, inclusive education information, our contacts. In the initial product development stage of E-Smart Inclusive, researchers developed it according to the list of features at the planning stage with materials in the form of laptops, servers, domains, and frameworks.